Modality use in joint attention between hearing parents and deaf children - Depowski, Nicole; Abaya, Homer; Oghalai, John; Bortfeld, Heather (Frontiers in Psychology, 2015)
The present study examined differences in modality use during episodes of joint attention between hearing parent-hearing child dyads and hearing parent-deaf child dyads. Hearing children were age-matched to deaf children. Dyads were video recorded in a free play session with analyses focused on uni- and multimodality use during joint attention episodes. Results revealed that adults in hearing parent-deaf child dyads spent a significantly greater proportion of time interacting with their children using multiple communicative modalities than adults in hearing parent-hearing child dyads, who tended to use the auditory modality (e.g., oral language) most often. While these findings demonstrate that hearing parents accommodate their children's hearing status, we observed greater overall time spent in joint attention in hearing parent-hearing child dyads than hearing parent-deaf child dyads. Our results point to important avenues for future research on how parents can better accommodate their child’s hearing status through the use of multimodal communication strategies.